Using YouTube videos as teaching media in improving students’ speaking skill - Suloso, Luluk Wiji Asti; Sakina, Rahma (ELT in Focus, 2023)
The purpose of this study is to examine students' perceptions of using YouTube videos to improve their English language skills and to examine the use of YouTube videos to improve students' language skills. This study used a mixed methods approach with a research design survey using a questionnaire research instrument and a quasi-experimental study research design using pre-test, treatment and post-test research instruments. This research was conducted at Bintara Vocational High School, Rancaekek in two classes, namely the experimental class and the controlled class. When analyzing the results of data collection, the pre- and post-tests as well as the results obtained were analyzed using the NCSS 2021. The data collection results showed positive results in using YouTube videos in improving students' speaking skills. Most students have a good perception of these media, but some have a neutral perception. Additionally, this study shows an improvement in speaking skills, meaning that the use of these media is effective. The results of this research are intended to provide an overview and information for English teachers who use YouTube videos as teaching media, especially when learning speaking.